High Andean Woody Plants, between Nursing and Competition Effects in a High Andean Polylepis Forests. Issue 1 (1st April 2022) - Alvarez-Montalván, C; Parra, C; Alvarez, J; Córdova-Mendoza, P; Julian-Laime, E; Laredo, I
Abstract: The diversity of Plants in the Andes is a complex stochastic network, this diversity is characterized by being distributed in three main families: Asteraceae, Poaceae and Rosaceae. The first two are the most diverse and have the Gynoxis and Chusquea genera respectively as the most dominant woody individuals in the last altitudinal floors above 3200 m. a. s. l. However, the Rosaceae family has less richness, it includes the genus Polylepis, present in the last tree line limit above 4300 m.a.s.l. This is the case of mono-specific forests of Polylepis rodolfo-vasquezii, a species highly threatened by anthropogenic impacts such as logging, burning, and llama-sheep farming. These forests are relict and generate a nurse effect, which allows the existence of important diversity such as Gynoxis nitida, Miconia latifolia, Bomarea dulcis and Displostephium rupestri and Brachyotum rostratum. However, the impacts generate complex plants diversity responses, where the nurse effect can become into a competition effect, especially with Gynoxis nítida, which can take advantage of the ecological niche to promote the increase in abundance of its young individuals against those of P. rodolfo-vasquezii, which is reduced by anthropic activities.